Early Nineteenth-Century New Yorkers and the Invention of New York City - François WEIL (E-REA)
This essay explores the « invention » of New York City in the antebellum era, or the parallel forms of cultural processes and elaborations that led to the emergence of a new sense of self-awareness in the city. It first evokes the contradictory ways in which a literary and artistic culture developed. It then attempts to reveal how New Yorkers translated their ancestral pride and identity feelings into historical and genealogical pursuits. It finally explores the way in which some works contributed to the creation of a new grammar, a new image, in order to draw the contours of the geography and sociology of the new metropolis.